2021
DOI: 10.3390/ijerph18136843
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Secondary Traumatic Stress of Nurses Caring for COVID-19 Patients in South Korea

Abstract: The secondary traumatic stress (STS) of nurses caring for COVID-19 patients is expected to be high, and it can adversely affect patient care. The purpose of this study was to examine the degree of STS of nurses caring for COVID-19 patients, and we identified various factors that influence STS. This study followed a descriptive design. The data of 136 nurses who had provided direct care to COVID-19 patients from 5 September to 26 September 2020 were collected online. Hierarchical regression analysis was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 46 publications
0
11
0
1
Order By: Relevance
“…There is a small number of studies showing that healthcare professionals during current pandemic experience moderate to high levels of STS ( Lee et al, 2021 ; Ranieri et al, 2021 ; Vagni et al, 2020 ). Contact with COVID-19 patients referred to as an aggravating factor for STS ( Orrù et al, 2021 .…”
Section: Introductionmentioning
confidence: 99%
“…There is a small number of studies showing that healthcare professionals during current pandemic experience moderate to high levels of STS ( Lee et al, 2021 ; Ranieri et al, 2021 ; Vagni et al, 2020 ). Contact with COVID-19 patients referred to as an aggravating factor for STS ( Orrù et al, 2021 .…”
Section: Introductionmentioning
confidence: 99%
“…They are at risk of diseases since they are providing care for nearly 24 h a day. Nurses are also subjected to a variety of mental strains and developing different psychological disorders as a result of caring ( Lee et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In South Korea, the studies related to psychological impact among nurses mostly reported only the mediating effects between burnout and self-efficacy, job performance, and emotional labors ( Kim et al, 2022 ; Lim et al, 2022 ), and identified factors affecting stress, not burnout ( Lee, Shin, & Hong, 2021 ), or explored the experiences of nurses working in COVID-19-designated hospital ( Lee & Lee, 2020 ). In addition, Kim and Lee's (2021) study compared the level of burnout between nurses with and without COVID-19–related tasks (56.0 % vs 31.5 %) excluding the factors affecting burnout in 2020, and the level of burnout is likely to mildly evolve over time ( Teo et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%